2020
DOI: 10.1101/2020.12.22.423903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paradoxical neuronal hyperexcitability in a mouse model of mitochondrial pyruvate import deficiency

Abstract: Neuronal excitation imposes a high demand of ATP in neurons. Most of the ATP derives primarily from pyruvate-mediated oxidative phosphorylation, a process that relies on import of pyruvate into mitochondria occuring exclusively via the mitochondrial pyruvate carrier (MPC). To investigate whether deficient oxidative phosphorylation impacts neuron excitability, we generated a mouse strain carrying a conditional deletion of MPC1, an essential subunit of the mitochondrial pyruvate carrier, specifically in adult gl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…These results suggest that newborn neurons might have a higher metabolic flexibility than previously thought if their preferential metabolic pathway is blocked. In line with this, it has been shown that several types of mature neurons are indeed able to sustain their functions by shifting their metabolism to other substrates, which can fuel OXPHOS when MPC is inhibited (59,64,65). We show that MPC1 cKO NSPCs are able to generate mature neurons in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…These results suggest that newborn neurons might have a higher metabolic flexibility than previously thought if their preferential metabolic pathway is blocked. In line with this, it has been shown that several types of mature neurons are indeed able to sustain their functions by shifting their metabolism to other substrates, which can fuel OXPHOS when MPC is inhibited (59,64,65). We show that MPC1 cKO NSPCs are able to generate mature neurons in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…These results suggest that newborn neurons might have a higher metabolic flexibility than previously thought if their preferential metabolic pathway is blocked. In line with this, it has been shown that several types of mature neurons are indeed able to sustain their functions by shifting their metabolism to other substrates, which can fuel OXPHOS when MPC is inhibited (DeLaRossa et al, 2022;Divakaruni et al, 2017;Ghosh et al, 2016). Indeed, we show that MPC1 ckO NSPCs are able to generate mature neurons in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with seizure development being a consequence of dysregulations generated either by reducing inhibitory (γ‐aminobutyric‐acid; GABAergic) or increasing excitatory (glutamatergic) signaling (Paz & Huguenard, 2015). Reducing energy capacity in glutamatergic neurones by conditional KO of the mitochondrial pyruvate carrier 1 (Mpc1) in glutamatergic but not GABAergic neurones can lead to increased seizures after GABA receptor antagonism by pentylenetetrazol or by KA‐induced glutamatergic stimulation (De La Rossa et al, 2022). Also reducing metabolism in glutamate and GABA neurones by using brain‐specific pyruvate dehydrogenase E1 subunit alpha 1 (Pdha1) KO mice can lead to increased susceptibility to seizures due to dysfunctional excitability in glutamatergic neurones (Jakkamsetti et al, 2019).…”
Section: Discussionmentioning
confidence: 99%